Intracellular cargo transport along multiple filaments with lane switching - Naruemon Rueangkham; Raymond J. Hawkins (Physical review. E, 2025)
Cargo transport mostly involves multiple molecular motors that move along cytoskeletal filaments. Such motors have the ability to detach and reattach on a filament and possibly switch onto another filament. Cargo transport by multiple motors on a single filament has been widely studied; however, cargo transport involving motors switching between filaments remains poorly understood. Here, we use lattice-based Monte Carlo simulations to investigate the properties of transport on multiple filaments, such as velocity, run length, and mean first passage time, compared with transport on a single filament. We provide an analytical expression for cargo velocity for multiple lanes as an extension of the expression for a single lane with a limited number of binding sites. We find this expression is sufficient to describe the force-velocity curves of clusters of motors on multiple lanes in our simulations. Our results show that cargoes being transported on multiple filaments move faster and further than those transported by a single filament. The time taken to deliver cargo to a given target distance is characterized by the mean first passage time, and our results showed a decrease in the time taken for transport on multiple filaments compared with single filaments. Moreover, we consider the effect of molecular motors' intrinsic properties in binding kinetics on their transport. Highly nonprocessive molecular motors with fast binding on and off rates, which are less persistent on filaments, transport cargo more slowly and for shorter run lengths compared with the same number of more processive motors with slow binding on and off rates. Consequently, nonprocessive motors with fast binding kinetics require more time than motors with slow binding kinetics to reach the same target.
Keywords: Advanced Materials and Mechanics; Cellular Automata and Applications; Microtubule and mitosis dynamics